Shape based Object Retrieval Technique for Vehicular Spare Parts - Hosur, Ravi; Dayanand G Savakar, Dr.; Madabhavi, Shilpa (International Journal of Engineering and Technology, 2018)
Shape based object retrieval technique is an application used for the automatic retrieval of vehicular spare parts based on the input image, this application can be useful in the automobile industry/shop for the retrieval of specific object from the group of objects. For the retrieval process first the database has been designed to store different shapes of nuts that are hexagon and square. With the application of median filter and wiener filters in the preprocessing step, the canny edge-detector for identifying the edges and to ascertain shape of the input and database images the convex hull approach is applied. This system is successful in retrieving the shape of the images which already exist in the database and the method results with the accuracy of 82.1875%
Keywords: Shape; objects; Vehicular parts; retrieval; automobile; edge.